Effect of 17 β-estradiol on calcium response to phytohaemagglutinin in human lymphocytes. Issue 1 (February 1990) - Bellini, Tiziana; Degani, Diana; Matteuzzi, Maurizio; Dallocchio, Franco
Abstract : Pre-treatment of human lymphocytes with 17 β -estradiol diminishes the increase in concentration of cytosolic free calcium after stimulation with phytohaemagglutinin. The effect is dependent on 17 β -estradiol concentration and on the preincubation time. The effect is not due to an interaction between 17 β -estradiol and phytohaemagglutinin, but appears to be a consequence of the binding of the hormone to the cell surface. The effect is specific for 17 β -estradiol, since the α isomer and other steroid hormones (progesterone, testosterone, diethylstilbestrol and 5α-androstan), have no effect. Since the effect of the 17 β -estradiol can be suppressed by treatment of lymphocytes with ouabain, it appears that the effect of estradiol on the rise of cytosolic calcium induced by phytohaemagglutinin is mediated by the (Na, K)-ATPase.